2016
DOI: 10.3892/etm.2016.3794
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the interaction between atorvastatin and selective serotonin reuptake inhibitors on the blood redox equilibrium

Abstract: Cardiovascular disease and depression often occur simultaneously in the same patient. Long-term polypharmacotherapy can lead to drug-induced oxidative stress. Data concerning the effects of concomitant treatment with atorvastatin and selective serotonin reuptake inhibitors (SSRIs) are lacking. The aim of the present study was to examine oxidative stress parameters in the blood of rats after 28 days treatment with atorvastatin combined with fluoxetine or paroxetine. The study was carried out on male Wistar rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Commercially available chemicals were purchased from Sigma-Aldrich and used without any further purication if not speci-ed elsewhere. NMR experiments were performed on a Bruker Avance III 400 spectrometer (frequencies: 400.13, 100.62, and 76.37 MHz for 1 H, 13 C, and 77 Se nuclei, respectively) equipped with a multinuclear inverse z-eld gradient probe head (5 mm). For data processing, TopSpin 4.0.8 soware was used and the spectra were calibrated using solvent signal ( .…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Commercially available chemicals were purchased from Sigma-Aldrich and used without any further purication if not speci-ed elsewhere. NMR experiments were performed on a Bruker Avance III 400 spectrometer (frequencies: 400.13, 100.62, and 76.37 MHz for 1 H, 13 C, and 77 Se nuclei, respectively) equipped with a multinuclear inverse z-eld gradient probe head (5 mm). For data processing, TopSpin 4.0.8 soware was used and the spectra were calibrated using solvent signal ( .…”
Section: Chemistrymentioning
confidence: 99%
“…From a biochemical and clinical point of view, the antioxidant effects of antidepressant agents were observed in animal models by measuring variations of GSH, malondialdehyde, nitric oxide and isoprostanes concentrations. [11][12][13] At molecular level, it has been highlighted that uoxetine exerts its antioxidant effects through a combination of mechanisms, involving direct ROS scavenging, modulation of the expression and functioning of enzymatic and non-enzymatic components of the endogenous antioxidant defence system, and/or enhancement of the serotonin antioxidant capacity. 14,15 Concerning the rst putative mechanism, the activity of uoxetine against ROS has been thoroughly studied from a biochemical and computational point of view.…”
Section: Introductionmentioning
confidence: 99%
“…It has been postulated that the capacity of fluoxetine to ameliorate the oxidative stress damage may be either due to a direct role of the molecule or achieved through the stimulation of some antioxidant enzymes. Oxidative stress can damage the cell through lipid peroxidation, DNA or protein oxidation, and mitochondrial damage [18]. In this connection, it must be pointed out that the central nervous system is composed of a high percentage of phospholipids, which can undergo peroxidation and generate ROS, and may eventually lead to potentially harmful conditions for cellular structures [19].…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, it must be pointed out that the central nervous system is composed of a high percentage of phospholipids, which can undergo peroxidation and generate ROS, and may eventually lead to potentially harmful conditions for cellular structures [19]. It has been demonstrated, mainly in preclinical but also in clinical studies, that fluoxetine provides a beneficial antioxidant effect through a combination of mechanisms: the inhibition of lipid peroxidation, an increase of glutaminergic transmission, the restoration of the normal metabolism of monoamines, the influence on ion balance, and a reduction of inflammation, which is connected to ROS production [18,20,21]. Kolla et al showed that amitriptyline and fluoxetine protect against oxidative stress-induced damage in rat pheochromocytoma (PC12) cells, contrasting the effects of H 2 O 2 [22].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased GPx activity in the animal brain suggests that compounds 4p and 3o prevent excessive ROS generation. GR is closely associated with GPx and plays an important role in protecting cells against oxidative damage by increasing the level of GSH by way of aerobic glycolysis . In our study, the increased activity of GR potentially indicates that there is an increased activity of the enzyme system that prevents oxidation.…”
Section: Discussionmentioning
confidence: 56%